Fouling community composition on a pilot floating solar-energy installation in the coastal Dutch North Sea - Mavraki, Ninon; Bos, Oscar G.; Vlaswinkel, Brigitte M.; Roos, Pauline; de Groot, Wim; van der Weide, Babeth; Bittner, Oliver; Coolen, Joop W. P. (Frontiers in Marine Science, 2023)
The increasing need for renewable energy has led to the transition of renewable energy devices to the marine environment. Currently, mainly offshore wind farms have been completely developed and are operational in the North Sea. The solar energy sector is also rapidly evolving and floating photovoltaics are continuously created and deployed. In this study, we investigated the colonisation patterns and community changes with time of fouling fauna on the first floating photovoltaics in the coastal Dutch North Sea. Samples were collected by divers from the underwater side of 4 floaters, coated with different anti-fouling techniques (Intersleek, GreenPowerNano PPDura, Finsulate and Pato) at two different moments, shortly after the deployment of the floaters and approximately a year later. In total, 72 fouling taxa were identified on the floaters, from which ca. 11% are known to be non-indigenous species for the region. The anti-fouling coating Intersleek seemed to work the most efficiently against fouling colonisation, since the fouling community sampled from this floater contained the least taxa. However, the small number of samples collected from the different floaters did not allow for a direct comparison between the anti-fouling coatings. The communities evolved with time, with young communities accommodating a larger number of individuals and old communities having less individuals but higher biomass, indicating that the organisms become bigger in size and compete for the available space. Nevertheless, the communities had not reached a stable climax yet, while this process might take multiple years due to the dynamic environment in which floating photovoltaics are deployed. Monitoring the fouling communities occurring on floating photovoltaics in the North Sea for a long-term is necessary to understand the effects of these new man-made structures on the marine environment, especially since floating photovoltaics are moving to offshore locations and will be possibly co-located with offshore wind farms in the future.